Comparison on the Effectiveness of Modular Learning in General Mathematics among the Senior High School Strands - Imee Borinaga Gutierrez (Southeast Asian Mathematics Education Journal, 2021)
This study aimed to compare the effectiveness of modular learning among senior high school strands and investigate the influence of students’ demographic profiles on their academic performances. Using One Way ANOVA, results showed a significant difference in the test scores obtained from the different strands. Results with Tukey HSD revealed that ABM performed best under modular learning, followed by STEM, GAS, ATS, and EIM, respectively. Pearson’s r revealed a significant correlation between student’s sex, monthly income, and parents’ employment status to students’ academic performance. Furthermore, the z test for two means determined that there was a significant difference in the scores of males and females. From these results, the researcher suggests that teachers handling TVL tracks must exert extra effort in delivering their mathematics lessons to close the gap in academic performance with the students from academic tracks.